THE IMPORTANCE OF FAMILY ENTREPRENEURSHIP IN INCREASING THE INCOME OF THE REGIONAL POPULATION - Fayzieva, Shirin Shodmonovna; Kuldasheva, Maftuna Musurmon qizi (THE INNOVATION ECONOMY, 2026)
This article examines the history of entrepreneurship, its modern forms, family entrepreneurship, employment issues, and its impact on income growth. It also highlights the key development trends in family entrepreneurship.